Evaluation of expression and serum concentration of anti-Mullerian hormone as a follicle growth marker following consumption of fennel and flaxseed extract in first-generation mice pups - Pourjafari, Fahimeh (BMC Complement Med Ther, 2021)
BACKGROUND: The aim of the present study was to assess the expression and serum level of AMH in first-generation female mice pups following fennel and flaxseed consumption. METHODS: Twenty pregnant NMRI mice were allocated into four groups including control (CTL), fennel (FV), flaxseed (LU) and FV+ LU. Sixty-four female offsprings after lactation period, received the same regimen as their mothers for 56 and 240 days. The ovarian follicles development, serum concentration of AMH, as well as gene and protein expression of AMH were evaluated in the female offsprings at post-natal day 56 (PND56) and 240 (PND240). RESULTS: The number of total growing follicles were raised in the FV group in compression to the all experimental groups. In contrast, LU group showed a marked decrease in their numbers. The highest level of serum AMH was seen in the FV-diet mice, whereas LU negatively affected it. The expression level of AMH also increased in the FV and FV + LU groups, while a reduction was observed in the LU group. As well, IHC data showed that the number of AMH-positive cells in almost ovarian follicles of FV and FV + LU-treated mice was in compared to those of the LU group. CONCLUSIONS: The overall effect of fennel treatment (alone and in combination with flaxseed) on ovary might be maintain primordial follicle storage through increased expression and serum level of AMH.